RESEARCH AND SIMULATION OF THE METHOD OF GENERATION OF THE FLOW OF MATRIX KEYS OF PERMUTATIONS AND THEIR CHARACTERISTICS FOR ENCRYPTION-MASKING OF VIDEO FRAMES - KRASILENKO, VLADIMIR; PIDLUBNYI, VLADISLAV; NIKITOVICH, DIANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Abstract - The article proposes and considers a method of generating and forming a stream of secret matrix keys (MK) in the form of permutation matrices. Based on consideration of the advantages of matrix models and algorithms for cryptographic transformations (CT) of images (I), textographic documents, aspects of the application of these matrix-type cryptosystems for creating blind electronic digital signatures (BEDS), masking of video frames, etc., the urgent need to form a set or a consistent series of secret keys. It is shown that, taking into account the peculiarities of crypto-transformations in multi-page, block ciphers, in matrix affine-permutation ciphers, a series of keys in the form of permutation matrices (PM) is necessary. To solve this problem, the article proposes a new approach and method of generating a series of MK (PM), based on the use of a series of sequential cryptotransformations of the base key using affine encryption when changing the keys of this cipher in accordance with the generated random digital sequence. Functionality and advantages of the method of generating a series of secret keys in the form of permutation matrices (PM) are demonstrated by model experiments in the Mathcad Professional software environment, screenshots from the created software modules. The properties of a series of MK PM were investigated using correlation and mutually equivalent normalized functions, which are more effective than correlation functions, and the adequacy and stability of the method were confirmed. The advantage of the proposed method and its matrix models and computational procedures is the consideration of the specificity of images and the ease of adaptation to different types and formats of images, the clarity and isomorphism of the visualization of both the components of the MK PM and the entire flow of keys. Formulas and algorithmic steps of procedures for creating a set of secret matrix keys and intermediate steps of closing, encrypting and decrypting images are given. The obtained results of modeling the method and the processes of creating a series of secret keys of matrix permutations in the Mathcad software environment confirmed the correct functioning and advantages of the proposed method.